Physiotherapy resources applied in patients submitted to abdominoplasty: a systematic review - Luciano Rodrigues da Silva Junior, Miguel; da Costa Cunha, Katiane; Domingas de Morais Alves de Almeida, Adriane; Soares Macedo, Felipe; Lucena da Silva, Marianne; Gouveia de Morais Sanchez, Eliane (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Abdominoplasty surgery is characterized by the removal of excess skin in the abdominal region, providing a desirable visual effect to the body. However, complications from the postoperative period can cause patient dissatisfaction and even risk to health, due to the inflammatory and scarring reaction due to the trauma caused by the surgical procedure. For the control and prevention of these effects, treatment with a physiotherapy professional is recommended, working with several resources. Objectives: To investigate the post-surgical interventions most used by physiotherapists in patients in the postoperative period of abdominoplasty, together with the resources used. Methods: This is a systematic literature review carried out using a comprehensive strategy in the PubMed, Embase, Cochrane, SCOPUS, Scielo, Web of Science and Google Scholar databases. Results: : Five studies, 3 clinical trials and 2 observational trials were carried out. included in the review. Of a total of 456 patients, 447 were female and 9 were male. The average age range was 18 to 67 years. The results showed that the most used resources with physiotherapeutic treatment include US, DML, Lymphotaping. Conclusion: It is concluded that the intervention of the physiotherapist is effective for the prevention of adverse symptoms such as hematomas, fibrosis, edema, swelling and inflammation, since the professional acts according to the scarring phases of the postoperative period.